Food Security, Food Systems, and Environmental Change - Ingram, John S.I.; Dyball, Robert; Howden, Mark; Vermeulen, Sonja J.; Garnett, Tara; Redlingshöfer, Barbara; Guilbert, Stéphane; Porter, John (2016)
With limited global resources, and in the face of environmental changes, meeting future food security challenges will first require a shift in thinking from just ‘producing food’ (and other sectoral interests) to ‘food systems.’ Solutions will need to be applied at local and regional levels, but still be interlinked through dialogue and alliances between all food system actors, including producers, processors, retailers and consumers, policy makers, NGOs, and other food system ‘influencers’ such as civil society groups. Though progress is being made, the current level of thinking around cross-sectoral dialogue and solutions is far from adequate. Policy strategies are required at all points in the system—on both the demand and supply side. While constructive engagement with industry and individuals is crucial, change is essentially being left up to voluntary actions. Future solutions should aim to find synergies between climate mitigation and adaptation and between health and environmental goals, with inevitable trade-offs that will need careful management. However, a holistic approach should also create opportunities that may help to smooth the transition from business-as-usual to a more sustainable food system.